Reprodução vegetativa e efeitos da densidade de uma Poaceae invasora sobre espécies nativas. - Michelan, Thaísa Sala (2016)
The biodiversity of aquatic and terrestrial ecosystems is being reduced at rates never before detected in the geological history of the planet. The threats have diverse backgrounds, including the destruction of habitats, pollution and introduction of species. The last one, is considered one of the most important factors influencing extinctions, although its effects are discussed to occur simultaneously to other causes. In Brazil, studies show that populations of exotic macrophytes with high invasive potential have grown in reservoirs and in natural aquatic ecosystems. For example, the African Poaceae Urochloa arrecta (Hack. Ex T. Durand & Schinz) Morrone & Zuloaga is recorded in high frequency and abundance in aquatic environments. The effects that this Poaceae cause in the structure of native populations and communities are well known, but the factors that regulate its invader potential via vegetative reproduction and its effects on growth and sexual reproduction of some natives? species are poorly studied. In this context, this tesis consists of three sessions. In the first, we tested the differences of U. arrecta sprouts growth from propagules derived in different parent plants sizes, positions and biomass. The results showed that the origin of propagules (small or large parent plant) is more important that their position in the plant and, in some cases, even more important than the biomass of propagules, as determining the length of biomass and new sprouts of U. arrecta. In the second session we evaluated experimentally the effects of the density of U. arrecta on the success and development of two native species of aquatic macrophytes (Pontederia cordata L. and Leersia hexandra Sw.). The data showed that biomass and length?s of the native plants decreased with increasing biomass of the invasive species, demonstrating that the competition between natives and U. arrecta depends on the exotic density. Moreover, the two species showed different strategies related to competition for nutrients or light when they interacted with U. arrecta. In the third session, we tested experimentally the effect of the competition of U. arrecta on the cost of reproduction of two native species of aquatic macrophyte (Pontederia cordata and Eleocharis montana (Kunth) Roem. & Schult). The results of this study showed that increased competition between invasive and natives species caused a decreasing of biomass and reproductive structures of native species. However, despite the decrease of total reproductive effort, in low to moderate densities of U. arrecta, both native species increased the biomass? relative allocation to reproduction and shortened the time required for issuing a first flower.